Restoration planning for climate change mitigation and adaptation in the city of Durban, South Africa. Issue 1 (1st January 2018) - Mugwedi, Lutendo F.; Ray-Mukherjee, Jayanti; Roy, Kathryn E.; Egoh, Benis N.; Pouzols, Federico M.; Douwes, Errol; Boon, Richard; O'Donoghue, Sean; Slotow, Rob; Di Minin, Enrico; Moilanen, Atte; Rouget, Mathieu
ABSTRACT: Effective planning of a large-scale restoration project is challenging, because of the range of factors that need to be considered (e.g. restoration of multiple habitats with varying degradation levels, multiple restoration goals and limited conservation resources). Ecological restoration planning studies typically focus on biodiversity and ecosystem services, rather than employment and other co-benefits. Robust Offsetting (RobOff), a restoration planning tool, was used in a forest restoration project in Durban, South Africa, to plan forest restoration considering a mosaic of habitats with varying levels of degradation, diverse restoration actions, a limited budget and multiple (biodiversity, carbon stock and employment) goals. To achieve this, the restoration action currently being implemented (= current action ) was compared to three restoration alternatives. The three restoration alternatives included (1) natural regeneration action ; (2) carbon action ; and (3) biodiversity action . The results supported biodiversity action as most beneficial in terms of maximizing biodiversity, carbon storage and job creation. Results showed that investing in biodiversity action is preferable to the status quo. RobOff ensured optimal allocation of limited resources to actions and habitats that have a potential to achieve higher biodiversity, carbon storage and job creation.